Systematic review and meta-analysis: bezafibrate in patients with primary biliary cirrhosis [Erratum] - Yin Q; Li J; Xia Y; Zhang R; Wang J; Lu W; Zhou Y; Zheng Y; Abudumijiti H; Chen R; Chen K; Li S; et al. (Dove Medical Press, 2015)
Yin Q, Li J, Xia Y, Zhang R, et al. Drug Design, Development and Therapy. 2015;9:5407–5419. On page 5410, Figure 2 was wrongly labelled as Figure 3. On page 5410, the Notes for Figure 1 should be: + indicates low risk, - indicates high risk, and ? indicates this is unclear.    View original article by Yin et al.